Up South in the Ozarks : dispatches from the margins - Blevins, Brooks, 1969- (The University of Arkansas Press, 2022)
"Up South in the Ozarks: Dispatches from the Margins is a collection of essays from Brooks Blevins that explore southern history and culture using [the] author's native Ozarks region as a focus. From migrant cotton pickers and fireworks peddlers to country store proprietors and shape-note gospel singers, Blevins leaves few stones unturned in his insightful journeys through a landscape 'wedged betwixt and between the South and the Midwest - and grasping for the West to boot"--